(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
Following the break-up of the state monopoly on audiovisual media in Turkey in 1990, the commercial television industry quickly became aware of the audience’s demand for domestic productions and home-made dramas. Throughout the 2000s, a television drama sector emerged, supplying a substantial amount of dramas not only to the domestic market, but also to a regional audience in the Middle East, Central Asia and Balkan countries. Although the lively market fosters an expanding “drama economy”, it still has some structural problems and weaknesses. Yet, the actors of the sector and the authorities are becoming more aware of what the market promises, culturally and politically, in addition to its economic value. Now, the drama industry is often assessed in terms of its “geo-cultural” significance or “soft-power.” Big producers even argue that the sector has become a global actor competing with Hollywood and Bollywood. It is a fact that Turkish dramas affect masses in neighbouring regions, reinforcing the “image” of the country and stimulating regional tourism. However, the claim that Turkish drama industry has become a competitive power in the international media market needs further and thorough research.